DNA fingerprinting : an introduction - Kirby, Lorne T., 1938- (Breakthroughs in molecular biology, 1990)
DNA fingerprinting is a revolutionary technique that enables law enforcement agencies, diagnostic laboratories and research scientists to identify minute pieces of tissue, to determine parentage and other biological family relationships. This is a study of its applications.